Цензурний контроль творів М.Грушевського та В.Винниченка в УСРР–УРСР - Шаповал, Ю.; Федотова, О. (Український історичний журнал, 2021)
Мета дослідження полягає у висвітленні практики цензурування творів
М.Грушевського та В.Винниченка в радянській Україні. Методологія ґрунтується на
принципах історизму, науковості, системності. Задля досягнення поставленої мети
застосовано методи: історико-генетичний, проблемно-хронологічний, джерелознавчого
аналізу, ретроспективний, аналітичний. Наукова новизна та висновки. Комплексно
розглядається практика цензурування праць М.Грушевського й В.Винниченка, а також
уводиться в науковий обіг ряд архівних джерел. Констатується, що твори згаданих авторів
перебували під пильною увагою впродовж усього радянського періоду. Показано, що
перші масштабні конфіскації органами цензури праць М.Грушевського було здійснено в
1920–1923 рр. у контексті контролю української літератури, що надходила з-за кордону.
Зазначено, що художні твори В.Винниченка та студії М.Грушевського практично до кінця
1920-х рр. видавалися в УСРР і були ще відносно доступними в наукових бібліотеках.
На етапі 1930-х рр. книжки В.Винниченка вилучали та знищували внаслідок стихійних
бібліотечних «чисток». Установлено, що централізоване обмеження видань цих авторів
розпочалося після Другої світової війни. Твори вилучалися у ході «чисток» бібліотечної і
книготорговельної мереж республіки, включно з букіністичним ринком. У другій половині
1940-х рр. усі книги М.Грушевського та В.Винниченка було тотально заборонено, їх
передали на зберігання в бібліотечні спецфонди. Основним арґументом стала належність
авторів до «буржуазно-націоналістичного табору». Заборонялося посилатися на
праці М.Грушевського та включати їх до бібліографічних і довідково-енциклопедичних
видань (виняток становили посилання, зроблені з метою «розвінчання ідейно-ворожої
сутності»). У результаті студії вченого випали з наукового обігу, оскільки обмежувалися
до кінця 1970-х рр., зокрема на підставі усних розпоряджень контролюючих органів.
Констатовано, що твори В.Винниченка перебували у спецфондах майже до кінця існування
інститутів радянської цензури. The purpose of the study is to highlight the practice of censoring the works of M.Hrushevskyi
and V.Vynnychenko in the UkrSSR. The research methodology is based on the principles
of historicism, scientificity, system. To achieve this goal, the following methods were used historicalgenetic,
problem-chronological, source analysis, retrospective, analytical. The scientific novelty and
conclusions. Consists in a comprehensive coverage of the Soviet practice of censoring the works of
M.Hrushevskyi and V.Vynnychenko in UkrSSR, as well as the introduction of a number of archival
sources into scientific circulation. It is stated that the works of M.Hrushevskyi and V.Vynnychenko as
enemies of the communist regime were censored throughout the Soviet period. The authors shows that
the first large-scale confiscations by the bodies of censorship of the works of M.Hrushevskyi was carried
out in 1920–1923 in the context of the control of Ukrainian literature, which came from abroad. It is
indicated that the works of V.Vynnychenko and M.Hrushevskyi were published in the UkrSSR and were
even relatively available in scientific libraries. At the stage of the 1930s, V.Vynnychenko’s books were
withdrawn and destroyed as a result of spontaneous library “purges”. It is established that the centralized
restriction of publications of these authors began after the World War II. The works of these individuals
were seized during the “purges” of the library and bookselling network, in particular the bouquinistes
market. In the second half of the 1940s, all books authored by M.Hrushevskyi and V.Vynnychenko were
completely banned and transferred for storage to library special funds. The main argument regarding the
restriction of the authors’ books was their belonging to the “bourgeois-nationalist camp”. Censorship
also forbade referring to the works of M.Hrushevskyi and including them in bibliographic and
reference-encyclopaedic issues. As a result, the scientist’s works fell out of scientific circulation, as it was
restricted until the end of the 1970s, in particular, on the basis of oral orders from regulatory authorities.
V.Vynnychenko’s works were in special funds almost until the last moment of the existence of communist
censorship institutions. The writer’s creative legacy became available only in 1989.